2016
DOI: 10.1111/cge.12800
|View full text |Cite
|
Sign up to set email alerts
|

The promoter polymorphisms of receptor for advanced glycation end products were associated with the susceptibility and progression of sepsis

Abstract: Receptor for advanced glycation end products (RAGE) is considered a major pattern recognition receptor, which plays an important role in the development of sepsis. Increasing evidence showed an association between RAGE polymorphisms and the susceptibility to several inflammatory-related diseases. However, little is known about the clinical relationship between RAGE polymorphisms and sepsis. In this study, we analyzed the association of sepsis with three functional RAGE gene polymorphisms (rs1800624, rs1800625 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Although the pathological mechanism of sepsis remains unclear, numerous lines of evidence have demonstrated that variations in genes associated with the inflammatory immune response play vital roles in the pathomechanism and progression of sepsis [47]. Progress in genetic sequencing and association studies between different immunological profiles and disease outcomes may someday allow for genetic diagnosis and interventional treatment of sepsis, ultimately improving outcomes for critically ill patients [810].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathological mechanism of sepsis remains unclear, numerous lines of evidence have demonstrated that variations in genes associated with the inflammatory immune response play vital roles in the pathomechanism and progression of sepsis [47]. Progress in genetic sequencing and association studies between different immunological profiles and disease outcomes may someday allow for genetic diagnosis and interventional treatment of sepsis, ultimately improving outcomes for critically ill patients [810].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of work has demonstrated that many variations in genes associated with the inflammatory and immune responses contribute to the occurrence and progression of sepsis [47]. However, to the best of our knowledge, the clinical relevance of MCP-1 genetic polymorphisms to sepsis has not been determined, adequately.…”
Section: Introductionmentioning
confidence: 99%
“…Two variants located in the promoter region of RAGE were significantly associated with the risk of sepsis. In total, four studies on RAGE rs1800625-429 T/C were conducted by Zeng et al [19] and Shao et al [20]. The primary meta-analysis of the four studies showed significant associations between the risk of sepsis and RAGE rs1800625-429 T/C in all three genetic models (OR = 0.59, 95% CI = 0.45–0.73, P < 0.001 for the dominant model, OR = 0.47, 95%CI = 0.24–0.96, P = 0.04 for the recessive model, and OR = 0.61, 95%CI = 0.51–0.74, P < 0.0001 for the allelic model) with a high level of evidence.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SLE patients with neurologic disorder carrying CC or CG genotypes seem to exhibit relatively higher levels of expression S100B compared with those carrying the GG genotype. It is known that polymorphisms in the promoter region of certain genes might regulate their expression by altering the binding sites of transcription factors (Sun, et al , 2007; Shao, et al , 2017). We hypothesized that the synonymous SNP rs1051169 located in the exon of S100B may exert an influence on splicing, thereby affecting the levels of serum S100B, which ultimately potentiate S100B-mediated pro-inflammatory processes, increase SLE risk, and promote neurologic disorder development.…”
Section: Discussionmentioning
confidence: 99%